Structural change, environment and well-being: interactions between production and consumption choices of the rich and the poor in developing countries - Angelo Antoci; Paolo Russu; Elisa Ticci (Fondazione Eni Enrico Mattei (FEEM), 2008)
Vulnerability to scarcity or to reduction of natural capital depends on defensive substitution possibilities that, in turn, are affected by the availability of other productive factors. However, in several developing countries asset distribution tends to be highly skewed. Taking into ac- count these elements, this paper argues that environmental degradation may represent a push factor of economic development in an economy polarized into two main classes (the Rich and the Poor) and characterized by the following stylized facts: a) the main income source of the rural poor is self-employment in traditional activities highly depending on natural resources; b) labor remuneration in rural sector represents the basic opportunity cost for (unskilled) labor in the economy. Thus, given that environmental degradation reduces labor productivity of the rural poor, it may depress wages; c) production of the modern sector managed by the rich is less affected by depletion of natural resources because they can adopt defensive strategies that the poor cannot. They are able to defend themselves by partially substituting natural resources with physical capital accumulation and wage labor employment. We will show that, in this context, environmental depletion may benefit the modern sector through an increase in low cost labor supply and, in turn, it may stimulate economic transition. However the structural change is likely to result in an increase in inequality.
Keywords: D62; O11; O13; O15; O41; Q20; 330; Production; Consumption Choices; Welfare